2013
DOI: 10.1086/671138
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Dwarf Galaxy Survey

Abstract: The Dwarf Galaxy Survey (DGS) program is studying low-metallicity galaxies using 230h of far-infrared (FIR) and submillimetre (submm) photometric and spectroscopic observations of the Herschel Space Observatory and draws to this a rich database of a wide range of wavelengths tracing the dust, gas and stars. This sample of 50 galaxies includes the largest metallicity range achievable in the local Universe including the lowest metallicity (Z) galaxies, 1/50 Zsun, and spans 4 orders of magnitude in star formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(150 citation statements)
references
References 216 publications
10
140
0
Order By: Relevance
“…More specifically, studies of optical and UV luminosity functions found that dwarf galaxies can contribute significantly to the faint end of the luminosity function (e.g., Liu et al 2008;Alavi et al 2016). Madden et al (2013), using Herschel, provides a rich far-IR and submm photometric and spectroscopic database for local dwarf galaxies covering a large range in metallicity (Dwarf Galaxy Survey-DGS). Focusing on the Herschel PACS spectroscopic data of the DGS, Cormier et al (2015) found an increasing trend of [C II] luminosity with increased metallicity among the dwarfs, where they cover a large range of [C II] luminosites (10 4-9 L e ) and metallicities (1/50-1 Z e ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, studies of optical and UV luminosity functions found that dwarf galaxies can contribute significantly to the faint end of the luminosity function (e.g., Liu et al 2008;Alavi et al 2016). Madden et al (2013), using Herschel, provides a rich far-IR and submm photometric and spectroscopic database for local dwarf galaxies covering a large range in metallicity (Dwarf Galaxy Survey-DGS). Focusing on the Herschel PACS spectroscopic data of the DGS, Cormier et al (2015) found an increasing trend of [C II] luminosity with increased metallicity among the dwarfs, where they cover a large range of [C II] luminosites (10 4-9 L e ) and metallicities (1/50-1 Z e ).…”
Section: Resultsmentioning
confidence: 99%
“…A better agreement between the two can be achieved if a CO-dependent ratio of log ([C II]/CO) is applied to the CO luminosity function where galaxies with higher CO luminosity have lower [C II]/CO ratio compared to those with lower CO luminosity. Theoretically this might be explained by CO being photodissociated into C and C + in low dust and metallicity environments by a strong far-UV field from young stars (e.g., Wolfire et al 2010;Madden et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In the following, we consider local galaxies from the KINGFISH sample (Kennicutt et al 2011), the GOALS sample (Sanders et al 2003;Armus et al 2009), and the Dwarf Galaxy Survey (DGS; Madden et al 2013). Combining these samples allows us to cover a wide range in galaxy properties.…”
Section: The Sample Of Herschel Observed Local Galaxiesmentioning
confidence: 99%
“…The distribution of dust mass surface density is inferred from infrared data from the Herschel Dwarf Galaxy Survey (Madden et al 2013). We model the infrared spectral energy distribution (SED) between 70 and 500 μm using a modified blackbody, the Draine & Li (2007) model, and the Galliano et al (2011) model with an amorphous carbonaceous component (see Galametz et al 2010;Rémy-Ruyer et al 2015 for details).…”
Section: Atomic Gas and Dustmentioning
confidence: 99%